Огляд та аналіз засобів створення інтерфейсу мобільних додатків - Калина, О. М.; Колендовська, М. М. (ХНУРЕ, 2022)
Mobile technology is ingrained in our lives - we can now pay directly from the phone, the simplest built-in applications have replaced paper books, newspapers, wallet and calendar, music players, cameras, calculators and computers. This growing popularity of mobile devices has now forced business owners to turn their attention to the mobile market, which, although part of the Internet, plays by its own rules.